Cholesterol and Hedgehog Signaling: Mutual Regulation and Beyond - Xu, Shouying; Tang, Chao (Frontiers in Cell and Developmental Biology, 2022)
The Hedgehog (HH) signaling is one of the key agents that govern the precisely regulated developmental processes of multicellular organisms in vertebrates and invertebrates. The HH pathway in the receiving cell includes Patched1, a twelve-pass transmembrane receptor, and Smoothened, a seven-transmembrane G-protein coupled receptor (GPCR), and the downstream GLI family of three transcriptional factors (GLI1-GLI3). Mutations of HH gene and the main components in HH signaling are also associated with numerous types of diseases. Before secretion the HH protein undergoes post-translational cholesterol modification to gain full activity, and cholesterol is believed to be essential for proper HH signaling transduction. In addition, results from our group and others show the reciprocal effect that HH signaling functions in cholesterol metabolism as well as in cholesterol homeostasis, which provides feedback to HH pathway. Here, we hope to provide new insights into HH signaling function by discussing the role of cholesterol in HH protein maturation, secretion and HH signaling transduction, and the potential role of HH in regulation of cholesterol as well.